2018
DOI: 10.1093/mnras/sty179
|View full text |Cite
|
Sign up to set email alerts
|

Production and fate of the G ring arc particles due to Aegaeon (Saturn LIII)

Abstract: The G ring arc hosts the smallest satellite of Saturn, Aegaeon, observed with a set of images sent by Cassini spacecraft. Along with Aegaeon, the arc particles are trapped in a 7:6 corotation eccentric resonance with the satellite Mimas. Due to this resonance, both Aegaeon and the arc material are confined to within sixty degrees of corotating longitudes. The arc particles are dust grains which can have their orbital motions severely disturbed by the solar radiation force. Our numerical simulations showed that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 15 publications
0
15
1
Order By: Relevance
“…Moreover, we obtained arcs with longitudinal sizes similar to the observed ones, at least for Methone and Anthe. When also non-gravitational forces are considered the lifetime of the particles is size dependent, with grains larger than 5 µm surviving in the arcs of Methone and Anthe for 10 2 yr (Sun et al 2017), whereas particles of 10 µm have a lifetime of 26 yr in the arc of Aegaeon (Madeira et al 2018). These results together put constraints on the timescales for which gravitational and non-gravitational forces operate to remove particles from the arcs.…”
Section: Anglesmentioning
confidence: 97%
See 3 more Smart Citations
“…Moreover, we obtained arcs with longitudinal sizes similar to the observed ones, at least for Methone and Anthe. When also non-gravitational forces are considered the lifetime of the particles is size dependent, with grains larger than 5 µm surviving in the arcs of Methone and Anthe for 10 2 yr (Sun et al 2017), whereas particles of 10 µm have a lifetime of 26 yr in the arc of Aegaeon (Madeira et al 2018). These results together put constraints on the timescales for which gravitational and non-gravitational forces operate to remove particles from the arcs.…”
Section: Anglesmentioning
confidence: 97%
“…Hedman et al 2009). However, the consideration of non-gravitational forces have shown that most particles are removed from the arcs in timescales of dozens of years, depending on the size of the grain (Sun et al 2017;Madeira et al 2018;Madeira & Giuliatti Winter 2020), indicating that the origin and sustainability of the arcs is still a puzzle (see also Araujo et al 2016).…”
Section: Satellitementioning
confidence: 99%
See 2 more Smart Citations
“…The material ejected can feed a tenuos ring. By assuming the impactors mass flux at Neptune's region as F ∞ imp = 10 −17 kg/(m 2 s) and the mean velocity of the impactors as v ∞ imp = 3.0 km/s (Poppe 2016), we determined the mass flux F imp and velocity v imp of impactors enhanced by to the gravitational focusing of the planet through the algorithm described in Sfair and Giuliatti Winter 2012 andMadeira et al (2018). The mass production rate by an icy moon with radius R is (Koschny and Grün 2001; Krivov et al 2003) Figure 11 shows the mass production rate of the neptunian inner satellites Naiad, Thalassa, Despina, Galatea, Larissa and Proteus.…”
Section: Ring System Under Perturbative Forcesmentioning
confidence: 99%